Kajian Rantai Nilai Agribisnis Mete Kabupaten Wonogiri - Sayoga, A. Aru Hadi Eka (JURNAL MANAJEMEN AGRIBISNIS; Vol 10 No 2 (2022): Jurnal Manajemen Agribisnis, 2022)
Increasing the value chain of a commodity in a region can be a major factor in the development of the local economy in a region. The same is true for the cashew nut agribusiness in Wonogiri because Wonogiri Regency is the leading producer of cashew (Anacardium occindintale) in Central Java Province with production approaching 90% of the total production in Central Java. Therefore, it is necessary to study the value chain of cashew nut production as the main commodity driving the economy of Wonogiri Regency along with the actors involved, critical points, and obstacles in it so that the objectives of this research can be achieved. With a qualitative descriptive approach, this research makes more use of field observations and surveys, and primary data is the main data source. The results obtained are that obstacles are still found in each value chain both at the input, production, collection, processing, and marketing stages, but efforts to overcome obstacles have been formulated since input, namely through efforts to strengthen institutional systems and farmer’s group management, product diversification and produce derivative products, as well as coaching and mentoring managerial governance, accounting and marketing techniques for cashew agribusiness actors .